The role of plasmacytoid dendritic cells in gut health - Won, Hye Yeon; Lee, Ju Young; Ryu, Dahye; Kim, Hyung Taek; Chang, Sun Young (Immune Network, 2019)
Plasmacytoid dendritic cells (pDCs) are a unique subset of cells with different functional characteristics compared to classical dendritic cells. The pDCs are critical for the production of type I IFN in response to microbial and self-nucleic acids. They have an important role for host defense against viral pathogen infections. In addition, pDCs have been well studied as a critical player for breaking tolerance to self-nucleic acids that induce autoimmune disorders such as systemic lupus erythematosus. However, pDCs have an immunoregulatory role in inducing the immune tolerance by generating Tregs and various regulatory mechanisms in mucosal tissues. Here, we summarize the recent studies of pDCs that focused on the functional characteristics of gut pDCs, including interactions with other immune cells in the gut. Furthermore, the dynamic role of gut pDCs will be investigated with respect to disease status including gut infection, inflammatory bowel disease, and cancers.
Keywords: Gut; Host defense; Immune tolerance; Plasmacytoid dendritic cell; Type I interferon